Sequential incremental doses of bisacodyl increase the diagnostic accuracy of colonic manometry. Issue 11 (23rd June 2016) - Borrelli, O.; Pescarin, M.; Saliakellis, E.; Tambucci, R.; Quitadamo, P.; Valitutti, F.; Rybak, A.; Lindley, K. J.; Thapar, N.
Abstract: Background: Colonic manometry is the standard diagnostic modality for evaluating colonic motility in children. Intraluminal bisacodyl is routinely used to trigger high‐amplitude propagating contractions (HAPCs), a feature of normal colonic motility. Usually, only a single dose (0.2 mg/kg) is suggested. We retrospectively explored whether the use of an additional higher (0.4 mg/kg) dose of bisacodyl increases the yield of colonic manometry. Methods: In 103 children (median age: 8.8 years, range 3.2–15.7 years) with a diagnosis of slow transit constipation, colonic motility was recorded for 1 h before and 1 h after each of two incremental doses of bisacodyl (low, L, dose: 0.2 mg/kg, max 10 mg; high, H, dose: 0.4 mg/kg, max 20 mg) and the characteristics of HAPCs analyzed. Key Results: High‐amplitude propagating contractions were seen in 85 children. H dose significantly increased the proportion of patients with fully propagated HAPCs (H dose: 57/103 [55%], L dose: 27/103 [26%], p < 0.001), paralleling the significant decrease in the proportion with partially propagated HAPCs (H dose: 29/103 [28%], L dose: 47/103 [46%], p < 0.01). Mean HAPC number significantly increased throughout the colon at H compared to L dose (7.2 ± 5.05 vs 5.6 ± 5.1, p < 0.05). Finally, the proportion of patients with normal pressure wave morphology of HAPCs significantly increased with higher dose (H dose: 55/85 [65%], L dose: 27/85 [32%], p < 0.001). Conclusions & Interferences: An additional higher dose of bisacodyl during colonic manometry improves colonic neuromuscular function suggesting its use might improve interpretation and decision making in children with slow transit constipation. Abstract : We retrospectively explored whether the use of sequential incremental dose of bisacodyl given during the colonic manometry increases the yield of the test. An additional high dose of bisacodyl improves colonic neuromuscular function by increasing the proportion of patients with fully propagated high‐amplitude propagating contractions (HAPCs) and their morphology. Our data suggest that the use of sequential incremental dose of bisacodyl during colonic manometry might significantly impact the management of children with refractory slow transit constipation.